2018
DOI: 10.22146/ijbiotech.32445
|View full text |Cite
|
Sign up to set email alerts
|

Amylolytic ability of bacteria isolated from termite (Coptotermes sp.) gut

Abstract: BSR 2, BSR 3, BSR 8, and BSR 9, different bacteria isolated from the termite gut, have been shown to possess cellulolytic activities, but their amylolytic ability has heretofore been unknown. This study attempted to fill in this knowledge gap. The formation of a clear zone using the iodine test showed that the bacteria were able to produce and secrete amylase. Based on the results, the best cultivation times for strains BSR 2, BSR 3, BSR 8, and BSR 9 were 6, 3, 2, and 2 d, respectively, yielding amylase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The measurement of protein concentration was done using spectrophotometric method with direct absorbance at wavelength 280 nm using a standard curve BSA (Bovine Serum Albumin) and using sterile double-distilled water as the blank (Mulyani et al, 2018).…”
Section: Total Protein Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of protein concentration was done using spectrophotometric method with direct absorbance at wavelength 280 nm using a standard curve BSA (Bovine Serum Albumin) and using sterile double-distilled water as the blank (Mulyani et al, 2018).…”
Section: Total Protein Concentrationmentioning
confidence: 99%
“…In the other side, four different bacteria originated from termit gut have also been reported to possess cellulolytic ability (Janatunaim et al, 2015b). Mulyani et al (2018) identified them as Pseudomonas alcaligenes (BSR 3), Brevibacillus parabrevis (BSR 8), and Brevibacillus sp. (BSR 9), while BSR 2 is still unidentified.…”
Section: Introductionmentioning
confidence: 99%